Personal Groundnut Separation Machine for Local Farmers (GS Machine) - Syahril, Syahfinizam; Muhyiddin, Mohammed (MNNF Publisher, 2021)
Applying improper crop cutting techniques can result in loss and damage to crop harvesting. The process of pruning crops from roots like peanuts can be done manually or mechanically. The mechanical cutting process is performed using a threshing machine. Studies have shown that the machine is rarely detected in the area. Purpose of this study is to create or develop ideas of cropping machines for separating crops from root. With this idea, the farmers can easily segregate their crops from roots easily. This research used the knowledge of farmers about existing machine and the results is recorded as data to develop ideation to design a proper cropping machine. The responses analysis shows that ideation of designing the cropping machine is acceptable and recommended by most farmers besides studying important elements in designing the machine.